The Effects of Learner Development Based on VARK Learning Approach on Creativity and Achievement of Nursing Students - Tanupabrungsun, supawan; Oatme, Sakawduean; Lertsakornsiri, Maleewan; Ritthapanya, Nutchaporn; Panyawarakom, Chayamon (NU Journal of Nursing and Health Sciences, 2023)
This research was Quasi-Experiment to study the effect of teaching management according to learning style for the ability to develop creative thinking and academic achievement of nursing students. The objectives of this study were 1) to study the VARK learning characteristics of first year nursing students, 2) to compare the scores of creative before and after the development of learners by creating a set of knowledge linking games and mind mapping of anatomy. and physiology 3) to compare the mean achievement scores before and after Developing students by creating a set of games to link knowledge and mind mapping anatomy and physiology subjects. The poupulation were 130 first year nursing students selected by purposive sampling. The samples were divided into two groups of 65 people each to be the experimental groups. Games and group 2 used a mind mapping learning style, a research tool as a measure of creativity. The Learning Characteristics Assessment Scale (VARK) and the Anatomy and Physiology Achievement Scale. Our instruments were validated with the content validity of .76 and reliability of .74 using Kuder-Richardson KR20 method. The data were analyzed using descriptive statistics and an independent t-test. The results showed the differences in VARK learning styles: Group 1 was Visual (V) = 31.11%, Aural (A) =31.11%, and Group2 was Aural (A) = 32.65% and Kinesthetic (K) = 30.61 % . The results also showed that while the pre-experiment creative thinking of the two sample groups was different (t=2.38, p = .019), there was no statistical difference after the experiment (t=.716, p=.475). In terms of academic achievement, there was no difference before and after the experiment (t = 1.292, p= .199). We concluded that the VARK-based learning approach had effects on creative thinking but not academic achievement. Assessment of previous learning experience is valuable in determining the impact of learning outcome for education management.